Chapter Storie e memorie della prima generazione di educatrici ed educatori dei nidi in Toscana - Macinai, Emiliano (Studi e saggi, 2019)
This contribution describes some steps of a research, by its nature constantly in progress, which has seen us engaged on several occasions in recent years, namely the collection and sharing of the stories and memories of Tuscan male and female educators. The contribution namely focuses on the intersections with Public History, a discipline or approach to history which is now rapidly consolidating in Italy as well.